Implementasi Kurikulum Merdeka Dalam Meningkatkan Mutu Pendidikan - Tesi Sukaesi; Suci Nuranika; Shyltia Putri; Merika Setiawati; Hendri Budi Utama (CV. ITTC INDONESIA, 2025)
The purpose of the curriculum is to provide better education to teachers and students so that they are more flexible, contextual, and focused on developing their skills and abilities. This study aims to understand how curriculum implementation can improve the quality of education by using qualitative research methods based on data analysis (library). Information is taken from books, articles, and scientific journals. The research findings show that the Merdeka curriculum can encourage more active learning, which is characterized by creativity and innovation that can inspire students to learn. Teachers are encouraged to improve their professional skills in teaching activities so that the quality of education can be improved.